Financial feasibility planning for one million hectares program to transition to low-emission rice in Vietnam and access to carbon credit markets - Iacobescu, Gabriela; Yu, Hye-in; Mello e Castro, Maria Ana; Brandon, Matthew; Verbeek, Midas; Saha, Souravi (International Rice Research Institute, 2024)
Traditional rice farming systems contribute considerably to greenhouse gas (GHG) emissions globally and in Vietnam, but they also offer a large potential for emission reductions. As part of the national strategy of Vietnam to reduce GHG emissions, the government has recently launched the ‘One Million Hectares of High Quality, Low-Emission Rice’ project (1Mha). The goal of our report is to assess the financial feasibility of this project. In order to do so we looked into to the requirements for scaling up the VnSAT that depend on the coordination between different stakeholders, strategies for dissemination of knowledge, the political context of carbon markets and the development of a reliable MRV system. We also investigated the current and future risks for the implementation of the project and its financial feasibility. This analysis resulted in a number of risks and barriers that range from Financial to Technological. In the cost-benefit assessment, the net annual revenue and the emission reductions were calculated for a business-as-usual (BAU) and 1MHa project scenario for the 1MHa. In the long-term, the project is projected to be profitable and is predicted to contribute an emission reduction of 38.1% over its 21-year lifetime, although it remains unclear whether carbon credit revenue is still feasible while meeting NDC requirements by the 2030 target.